Smart Business Strategies in Waqf Asset Management : Innovative Solutions for Risk Mitigation - Mutiara (ICO EDUSHA, 2024)
This study aims to identify and analyze smart business strategies that can be applied in waqf asset management as well as innovative solutions to control emerging risks. Waqf assets have great potential to support social and economic development, but their management faces various challenges, including financial, regulatory, and operational risks. This research approach uses a qualitative method with case studies of several waqf management institutions in Indonesia. Data were collected through in-depth interviews, participatory observation, and documentation studies. The results show that the implementation of smart business strategies, such as asset diversification, utilization of digital technology, and collaboration with the private sector, can improve management efficiency and resilience to risk. In addition, innovative solutions such as sustainable business model development and data-driven risk mapping have also proven effective in mitigating the challenges faced by waqf managers. The findings are expected to serve as practical guidance for waqf institutions in improving governance and optimizing the potential of waqf assets in a sustainable manner. This research provides new insights into the practice of waqf asset management by offering an approach that considers not only efficiency, but also long-term resilience through innovative strategies. By utilizing digital technology and cross-sector collaboration, waqf institutions can be more adaptive to changing market dynamics as well as regulatory and operational challenges. The solutions proposed in this study, such as asset portfolio diversification and sustainable business models, provide the basis for the development of a resilient waqf management system capable of optimally supporting economic and social development. The results of this study are expected to make a significant contribution in building the foundation of a more professional and adaptive waqf asset management, so that waqf assets can be managed productively and provide maximum benefits to society.          Keywords : business strategy, waqf assets, innovation, risk management, sustainability